Vasoproliferative Tumor Secondary to Sarcoidosis-Associated Intermediate Uveitis - Sara Abdel Jalil; Tareq Jaouni; Radgonde Amer (Türk Oftalmoloji Dergisi)

(untitled)
We report the visual and clinical outcomes of a middle-aged woman who presented with exudative retinal detachment (ERD) secondary to a vasoproliferative tumor (VPT) in an eye with sarcoidosis-associated intermediate uveitis. A 55-year-old woman previously diagnosed with sarcoidosis presented with decreased vision in the left eye (LE). Visual acuity in the LE was counting fingers. She had active vitritis, and a peripheral retinal vascular mass was noted in the superotemporal periphery. The mass was associated with ERD involving the posterior pole. The patient was managed with systemic and intravitreal steroids, and cyclosporine was subsequently added as a steroid-sparing agent. Because of recurrence of ERD, the patient underwent pars plana vitrectomy, and cryotherapy and laser photocoagulation were applied to the VPT. Two months postoperatively, visual acuity in the LE improved to 6/10. There was marked regression of the VPT and total resolution of the ERD. In conclusion, we report a favorable visual and clinical outcome in a patient with VPT-associated ERD who responded to a combination of medical therapy and surgical intervention. VPT may lead to different remote complications, so timely diagnosis of these tumors and proper management of their complications is warranted.